Review of the dynamic stiffness method for free-vibration analysis of beams. Issue 2 (19th December 2019) - Banerjee, J R Banerjee
Abstract: The application of the dynamic stiffness method (DSM) for free-vibration analysis of beams is surveyed in this paper. The historical development of the DSM, which has taken place in several stages, is discussed in detail with reference to the free-vibration problems of beams. In particular, the suitability of the DSM in solving the free-vibration problems of beams through the application of the well-known Wittrick–Williams algorithm as a solution technique is highlighted. The literature concerning homogeneous isotropic metallic beams, for which the DSM is well established, is reviewed first, after which, with the rapid and ongoing emergence of advanced composite materials, the development of the DSM in solving the free-vibration problems of anisotropic beams is discussed. The free-vibration analysis of functionally graded beams using the DSM is also highlighted. The survey covers the DSM application for free-vibration analysis of a wide range of beams, including sandwich beams, rotating beams, twisted beams, moving beams and bending-torsion coupled beams, amongst others. Some aspects of the contributions made by the author and his research team are also highlighted. Finally, the future potential of the DSM in solving complex engineering problems is projected.